2023
DOI: 10.1101/2023.01.16.524255
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nr5a2is essential for morula development

Abstract: Early embryogenesis is driven by transcription factors (TFs) that first activate the zygotic genome and then specify the lineages constituting the blastocyst. While the TFs specifying the lineages of the blastocyst are well characterised, those playing earlier roles are ill-defined. Using mouse models of the TF Nr5a2, we show that Nr5a2 KO embryos arrest at the early morula stage and exhibit overt phenotypical problems such as altered lineage specification, frequent mitotic failure and substantial chromosome s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Hence, through the concomitant compensation of ESRRB downregulation by ESRRA up-regulation, GATA6 coordinates a switch between nuclear receptors to sustain Oct4 expression, maintain accessible those regulatory elements that were specifically controlled by ESRRB in ES cells, and broadly extend their function to regions targeted by GATA6. While the functions of nuclear receptors are redundant in pluripotent cells 63,64 , this and other studies indicate that their importance can also be hierarchized as changes in cellular contexts are implemented 75 . Whether the essential role of ESRRA is exclusively mediated by its direct enhancement of GATA6 activity or also indirectly via the control of Oct4 , or whether it is important for other regulations needed for differentiation and survival 76-78 , such as mitochondrial activity and lipid catabolism 79 , remains unclear.…”
Section: Discussionmentioning
confidence: 86%
“…Hence, through the concomitant compensation of ESRRB downregulation by ESRRA up-regulation, GATA6 coordinates a switch between nuclear receptors to sustain Oct4 expression, maintain accessible those regulatory elements that were specifically controlled by ESRRB in ES cells, and broadly extend their function to regions targeted by GATA6. While the functions of nuclear receptors are redundant in pluripotent cells 63,64 , this and other studies indicate that their importance can also be hierarchized as changes in cellular contexts are implemented 75 . Whether the essential role of ESRRA is exclusively mediated by its direct enhancement of GATA6 activity or also indirectly via the control of Oct4 , or whether it is important for other regulations needed for differentiation and survival 76-78 , such as mitochondrial activity and lipid catabolism 79 , remains unclear.…”
Section: Discussionmentioning
confidence: 86%
“…However, our data are fully consistent with a recent preprint showing that ZGA largely initiated normally in Nr5a2 maternal-zygotic KO embryos which were subsequently arrested at the morula stage, and maternal NR5A2 was dispensable for embryonic development. 50 These discrepancies likely arise from different approaches used in these studies.…”
Section: Discussionmentioning
confidence: 97%
“…Their data showed that while Nr5a2 knockdown or knockout did not significantly impact ZGA, it led to impaired activation of 4–8 cell stage genes and resulted in embryonic arrest at the morula stage. Similarly, Festuccia et al reported that Nr5a2 knockout embryos progressed beyond the two-cell stage but exhibited significant developmental delays and morphological abnormalities at the morula stage, highlighting its crucial role in morula development and first lineage specification [ 62 , 63 ]. We hypothesize that further studies using more specific inhibitors targeting Nr5a2 or the same genetic background mice may help resolve the debates about the role of Nr5a2.5.…”
Section: The Role Of Nr5a2 In Zgamentioning
confidence: 99%